Pathology of Female Cancers Precursor and Early-Stage Breast, Ovarian and Uterine Carcinomas (Springer Singapore, 2018)
This book focuses on precursor lesions, borderline lesions, and early carcinomas of female-specific organs from the standpoint of pathology. In 2012, the latest WHO Classification of Tumours of the Breast, 4th ed., was published and subsequently, in 2014, the WHO Classification of Tumours of Female Reproductive Organs, 4th ed., was published. In these fourth editions, several new concepts are addressed that were not described in the previous editions, and many of them are related to the awareness of the specific pathogenesis of tumors in female patients. Although some of these issues are still controversial, several paradigm shifts should be understood by medical scientists. Thus researchers, diagnostic pathologists, and clinicians must share current information about what is taking place in the field and what the next issue to resolve is. This volume greatly broadens the reader's understanding of the new concepts and paradigm shifts, as it includes informationon how to diagnose and make differential diagnoses on a practical basis and also provides a thorough explanation of the molecular-clinicopathologic basis of the new concepts. The book thus benefits gynecologists, breast surgeons, gynecologic-medical oncologists, and cytotechnologists.